Molecular characterization of Orf virus in goats in Gabon, Central Africa - Maganga, Gael D. (Virol J, 2016)
BACKGROUND: Orf or contagious ecthyma is a zoonotic viral infection with a potential serious health threat for the small ruminants industry as well as humans. It is currently emerging in new territories. RESULTS: Eight suspected clinical cases of pustular dermatitis in goats occurred in the rural area of Tebe, in south-eastern Gabon, in January 2013. The orf virus (ORFV) was detected by high-throughput sequencing on sera, buccal swabs and scab pool samples. It was confirmed in six out of eight sick goats by using specific PCR targeting the major envelope protein (B2L) and the orf virus interferon resistance (VIR) genes. Phylogenetic analysis revealed that the Gabonese strain and South Korean strains evolved from a common ancestor, suggesting an Asian origin of the ORFV’ Gabonese strain. CONCLUSIONS: This study provides the molecular detection of the ORFV strain involved in the cases of pustular dermatitis in goats and highlights its circulation in Gabon.